The decline of intelligence in America : a strategy for national renewal - Itzkoff, Seymour W. (Praeger, 1994)
Few doubt that the United States has slipped from its longstanding eminence as the world's wealthiest and most productive nation. The problem for the past thirty years has been the diagnosis of both the decline and then the cure. Literally trillions of dollars have been expended in futile programs to staunch the hemorrhaging of our economic wealth, jobs, educational achievement, and cultural elan.